2019
DOI: 10.3928/23258160-20181212-07
|View full text |Cite
|
Sign up to set email alerts
|

Trimanual Versus Unimanual 23-Gauge Vitrectomy in Patients With Diabetes: Limitations and Expectations

Abstract: BACKGROUND AND OBJECTIVE: To compare between trimanual and unimanual vitrectomy in complicated proliferative diabetic retinopathy (PDR). PATIENTS AND METHODS: A prospective, non-randomized, comparative study including patients with tractional retinal detachment (TRD), vitreous hemorrhage with TRD, and combined TRD with rhegmatogenous retinal detachment. The patients were allocated into two groups: the unimanual group with three-port vitrectomy and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Two, both published in the European Vitreoretinal Society (EVRS) Educational Electronic Journal, where irretrievable from Queen’s University library (Belfast, UK) and The British Library (London, UK) and could not be assessed. After full-text evaluation of all other studies, 38 (with 3839 eyes) were found eligible and included . Patients had a median (IQR) age of 52.2 (49.6-55.7) years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two, both published in the European Vitreoretinal Society (EVRS) Educational Electronic Journal, where irretrievable from Queen’s University library (Belfast, UK) and The British Library (London, UK) and could not be assessed. After full-text evaluation of all other studies, 38 (with 3839 eyes) were found eligible and included . Patients had a median (IQR) age of 52.2 (49.6-55.7) years.…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis of overall final VA included 20 studies (1526 eyes). The pooled final BCVA was 0.94 (95% CI, 0.82-1.05) logMAR (approximate Snellen equivalent, 6/53; 95% CI, 6/39-6/71) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The results are presented in Table 1. Overall, the quality of 21 studies was classified as high (4,6,8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), and five studies were determined to have moderate quality (3,5,7,9,10).…”
Section: Quality Assessment Of the Studiesmentioning
confidence: 99%
“…However, published reports indicate that 0.3%–23.6% of PDR patients still develop NVG even after PPV. 328…”
Section: Introductionmentioning
confidence: 99%
“…With the en bloc method, the AP traction is left untouched, using it as the "third hand", while with the bimanual method, the membrane is lifted with a pair of forceps in one hand, cutting the pegs with scissors with the other, aided by chandelier lighting. 18 The shaving technique is particularly useful for broad sheets of membrane with multiple, tightly spaced vascular pegs where the delamination technique would be very time consuming. The shaving technique is made possible by small gauge vitrectors (25-G or 27-G) where the ports are located very close to the tip.…”
mentioning
confidence: 99%